Investigating porous crystalline materials implanted with single metal sites or controlled metal clusters for catalysis by advanced electron microscopy - Ho, P-L (2023)
This thesis introduces characterising porous crystalline materials implanted with single metal sites or controlled metal clusters for catalysis, where several successful cases are provided to correlate the material microstructure with catalytic performance.